2019
DOI: 10.2320/matertrans.mf201923
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Phase Transformations under Severe Plastic Deformation by Torsion in Rotational Anvils

Abstract: Numerous experiments have documented that combination of severe plastic deformation and high mean pressure during high-pressure torsion in rotational metallic, ceramic, or diamond anvils produces various important mechanochemical effects. We will focus here on four of these: plastic deformation (a) significantly reduces pressure for initiation and completion of phase transformations (PTs), (b) leads to discovery of hidden metastable phases and compounds, (c) reduces PT pressure hysteresis, and (d) substitutes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
82
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 71 publications
1
82
0
2
Order By: Relevance
“…First, amorphization can occur in SiO 2 quartz by mere application of pressure and without straining, but the pressures are usually quite high in the range of 20‐30 GPa 59–61 . It was suggested that the continuous formation of grain boundaries, dislocations, and their pile‐up during the HPT process can theoretically result in localized stress/pressure concentration and nucleation of pressure‐induced crystalline or amorphous phases at lower pressures compared to the static compression 58,62 . Second, detailed TEM observations by the authors confirm that amorphization does not occur or its extent is small for the samples processed at room temperature or for the sample processed at 723 K for 1/4 turns, indicating the importance of strain and temperature in amorphization Third, HPT‐induced partial amorphization is not limited to quartz sand and similar phenomenon was reported in intermetallics, 63 multicomponent alloys, 64 and ceramics, 18 although HPT‐induced partial crystallization was also reported in some amorphous alloys 65,66 …”
Section: Resultsmentioning
confidence: 94%
“…First, amorphization can occur in SiO 2 quartz by mere application of pressure and without straining, but the pressures are usually quite high in the range of 20‐30 GPa 59–61 . It was suggested that the continuous formation of grain boundaries, dislocations, and their pile‐up during the HPT process can theoretically result in localized stress/pressure concentration and nucleation of pressure‐induced crystalline or amorphous phases at lower pressures compared to the static compression 58,62 . Second, detailed TEM observations by the authors confirm that amorphization does not occur or its extent is small for the samples processed at room temperature or for the sample processed at 723 K for 1/4 turns, indicating the importance of strain and temperature in amorphization Third, HPT‐induced partial amorphization is not limited to quartz sand and similar phenomenon was reported in intermetallics, 63 multicomponent alloys, 64 and ceramics, 18 although HPT‐induced partial crystallization was also reported in some amorphous alloys 65,66 …”
Section: Resultsmentioning
confidence: 94%
“…The elemental mixing improves with increasing the distance from disc center, indicating the importance of shear strain on mechanical alloying and controlling the phase transformation, in good agreement with earlier publications. [32][33][34][35] The microstructure of sample processed by HPT for ten turns was examined in detail using transmission electron microscopy (TEM), as shown in Figure 4, in different modes, such as bright-field imaging (Figure 4a), selected area electron diffraction (SAED) analysis (Figure 4b), dark-field imaging (Figure 4c), automatic orientation mapping (Figure 4d), and phase mapping ( Figure 4e) using an automatic crystal orientation and phase mappings (ASTAR device). Note that the phase map was overlaid with the reliability map in Figure 4e, and thus, the black regions in the image correspond to the phases that could not be identified with high reliability.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that HPT as a severe plastic deformation (SPD) method shows high potential to produce nanostructures, [30,31] control phase transformations, [32,33] and achieve solid-state reactions. [34,35] The method was used successfully by the group of authors to synthesize various kinds of nanostructured intermetallics in different systems, such as Al-Ni, [36] Al-Ti, [37] Al-Cu, [38] Al-Ti-Ni, [39] Fe-Ni, [40] Mg-Ti, [41,42] Mg-Zr, [43] Mg-Hf, [44] Mg-Ni-Pd, [45] and Mg-V-Cr. [46] It is worth mentioning that, following publication of two articles in 2004 [47] and 2007, [48] the HPT process became popular not only for processing [49][50][51][52][53] but also for synthesizing [54][55][56][57][58] various kinds of hydrogen storage materials.…”
Section: Introductionmentioning
confidence: 99%
“…Due to significant increase in the sticking zone, an increase in p max above 240-300 GPa leads to decrease in the maximum range of pressure and contact stress σ c at which plastic flow, Coulomb or plastic friction occur. The only way to increase these ranges for characterization of plastic flow and contact friction is to use torsion under a fixed force in rotational DAC, 12,15,22,[34][35][36] for which FEM simulations 29,37 show that the sticking zone is localized near the center.…”
Section: Resultsmentioning
confidence: 99%
“…obtained results have also applied importance for study of various sample materials within W gasket. Knowledge of the distributions of all (generally 12) components of stress and plastic strain tensors in a sample will allow study of their (instead of pressure alone) effect on phase transformations, chemical reactions, 12,[14][15][16][20][21][22][34][35][36][37] and various physical properties. In comparison with research under hydrostatic pressure, this will add up to 11 new dimensions to the parametric space for studying these processes, searching for new phases and materials, drastically reducing the required pressure for synthesis of new and known materials with unique properties, and understanding processes in the deep interiors of the Earth and other planets.…”
Section: Resultsmentioning
confidence: 99%